Miniaturized Multi-spurline Bandstop Filter Design with a Meandered Slot Lines - Shrestha, Bhanu; Shrestha, Surendra (Journal of the Institute of Engineering, 2016)
A multi-spurlines with meandered slot line bandstop flter is studied. A wideband width bandstop flter is designed and simulated on the basis of a Tef- lon substrate having thickness of 0.54 mm and a dielectric constant of 2.54. The wideband width is achieved even if the multi-coupling effects of multi-spurline are increased. The proposed bandstop flter has good S-parameter responses with good stopband characteristics. The insertion loss (S21) and return losses are 34.5 dB and 0.12 dB respectively. The wide band rejection depth increased by improving trans- mission zeros at 12 GHz. The wideband bandstop flter can be implemented to the X-band applications. The size of the designed bandstop flter is 5.8 mm × 3 mm. Journal of the Institute of Engineering, 2015, 11(1): 172-176